Futuristic Leadership’s Profile: A Best Practice of Malaysia’s State Religious Secondary School - Abdullah Shukri Mohamed Nor; Muhammad Faizal A. Ghani; Abd. Muhith (JIEMAN: Journal of Islamic Educational Management, 2022)
Leading and managing change in the field of education in the 21st century is often seen as a complex challenge, not only in terms of the change itself but also the knowledge, skills, and attitude of the principal as a school leader that is expressed in his leadership. This study was conducted to build a profile of the best leadership practices of the National Religious Secondary School principal. Qualitative research using the interview method was used to collect data. The study participants comprised two experts with more than 20 years of experience in the education field and were directly involved in managing the National Religious High School. The study's findings show that the study participants have a practical and effective approach to be applied by school principals. Precisely, the best practice of principal leadership in the context of futuristic leadership consists of professional leadership, collaborative culture in the organization, development of leadership competencies, enrichment of school data, consensus among stakeholders, and acceptance of diversity. Memimpin dan mengelola perubahan di bidang pendidikan pada abad ke-21 seringkali dipandang sebagai tantangan yang kompleks, tidak hanya dalam hal perubahan itu sendiri tetapi juga pengetahuan, keterampilan, dan sikap kepala sekolah sebagai pemimpin sekolah yang dituangkan dalam karyanya. kepemimpinan. Kajian ini dilakukan untuk membangun profil praktik kepemimpinan terbaik kepala Sekolah Menengah Keagamaan Nasional. Penelitian kualitatif dengan metode wawancara digunakan untuk mengumpulkan data. Peserta penelitian terdiri dari dua orang ahli yang telah berpengalaman lebih dari 20 tahun di bidang pendidikan serta terjun langsung dalam pengelolaan SMA Negeri. Temuan studi menunjukkan bahwa peserta studi memiliki pendekatan yang praktis dan efektif untuk diterapkan oleh kepala sekolah. Secara khusus, praktik terbaik kepemimpinan kepala sekolah dalam konteks kepemimpinan futuristik terdiri dari kepemimpinan profesional, budaya kolaboratif dalam organisasi, pengembangan kompetensi kepemimpinan, pengayaan data sekolah, konsensus antar pemangku kepentingan, dan penerimaan keragaman.